The somatotypes and body composition of elite track and field athletes and swimmers - Stankovic, D.; Pavlovic, R.; Petkovic, E.; Rakovic, A.; Puletic, M. (International Journal of Sports Science, 2018)
The research was carried out on a sample of 26 elite Serbian track and field athletes (age 20.3±4,45yrs; height 181±7,81cm; weight 73,7±14,15kg, BMI 22,4±3,21kg/cm²), 13 swimmers (age 17±2,47yrs; height 178,3±8,24cm; weight 68,7±11,03kg; BMI 21,5±1,98kg/m²) and 30 students of the Faculty of Sport and Physical Education in Niš (age 20,3±0,13yrs; height 180,1±1,56cm; weight 75,5±2,17kg; BMI 23,2±0,44kg/m²), all males, attending their first year at university (30), with the aim of determining their somatotype and body composition. The obtained results have confirmed that in the case of the athletes, we found several somatotypes: the balanced mesomorphic and endo-mesomorphic (30,8%), a central somatotype and ecto-mesomorphic somatotype (11,5%) and to a significantly smaller percentage, meso-endomorphic and meso-ectomorphic components (7,7%). In the case of the swimmers, three types of somatotypes were found: the balanced mesomorphic (46,15%), ecto-mesomorphic (30,77%) and meso-ectomorphic (23,08%) which defined a homogenous group. The students were defined by all forms of somatotypes, except the endo-ectomorphic (meso-endomorphic (33,33%), endo-mesomorphic (23,33%), while the other types were found in a much smaller percentage, which determined the heterogeneity of the group. The analysis of the body composition has indicated that all three components are greater among the students compared to the track and field athletes and swimmers, that is, that the students weigh more than the athletes, and the athletes weigh more than the swimmers. In the case of the track and field athletes, all three components are significantly greater among the throwers compared to the runners and jumpers, whose values are smallest. In the case of the swimmers, it was determined that BF% and FBM are greater for the butterfly style, while the NFBM is smaller compared to the other swimming styles. The multivariate analysis between the groups of athletes (track and field and swimmers) and the control group (students) for the variables BF%, FBM, NFBM, did not show any statistically significant differences, although the significance of the difference was right on the borderline value (p=0.058). At the univariate level, a statistically significant difference was noted between the group of athletes (track and field and swimmers) and the control group (students) for the variables BF%, FBM, NFBM. A statistically significant greater difference (p<0,05) was noted for BF% and FBM in favor of the students, while for the NFBM there is no statistically significant difference, which indicates that greater weight is a consequence of the greater amount of fat tissue.